Art crime in context - Oosterman, Naomi; Oosterman, Naomi; Yates, Donna; Yates, Donna (Studies in art, heritage, law and the market, 2023)
This book brings together empirical and theoretical case-study research on art and heritage crime. Drawn from a diverse group of researchers and professionals, the work presented explores contemporary conceptualisations of art crime within broader contexts. In this volume, we see 'art' in its usual forms for art crime scholarship: in paintings and antiquities. However, we also see art in fossils and in violins, chairs and jewellery, holes in the ground and even in the institutions meant to protect any, or all, of the above. And where there is art, there is crime. Chapters in this volume, alternatively, zoom in on specific objects, on specific locations, and on specific institutions, considering how each interact with the various conceptions of crime that exist in those contexts. This volume challenges the boundaries of what we understand as "art and heritage crimes" and displays that both art, and criminality related to art, is creative and unpredictable.